2006
DOI: 10.1002/lt.20806
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of clinical outcome in children undergoing orthotopic liver transplantation for acute and chronic liver disease

Abstract: The current United Network for Organ Sharing (UNOS) policy is to allocate liver grafts to pediatric patients with chronic liver disease based on the pediatric end-stage liver disease (PELD) scoring system, while children with fulminant hepatic failure may be urgently listed as Status 1a. The objective of this study was to identify pre-transplant variables that influence patient and graft survival in those children undergoing LTx (liver transplantion) for FHF (fulminant hepatic failure) compared to those patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 34 publications
(39 reference statements)
0
28
0
Order By: Relevance
“…This risk of death or graft loss increased substantially to 3.7 and 2.1 if the patient was also intubated, a finding substantiated by others. 2,23,24 The individual components of the PELD score were not predictive of outcome at 6 months, either in the multivariate analysis of only base line factors (with the exception of growth failure for patient survival) or in the multivariate models, including baseline and posttransplant complications. Although other studies have sought to find a relationship between PELD and posttransplant outcome, 19,25 in this large cohort of patient, it is not surprising that the PELD score, which was developed only as a predictor or waiting list mortality, 26 would not be significant predictor of posttransplant outcome in an analysis that includes posttransplant events.…”
Section: Discussionmentioning
confidence: 91%
“…This risk of death or graft loss increased substantially to 3.7 and 2.1 if the patient was also intubated, a finding substantiated by others. 2,23,24 The individual components of the PELD score were not predictive of outcome at 6 months, either in the multivariate analysis of only base line factors (with the exception of growth failure for patient survival) or in the multivariate models, including baseline and posttransplant complications. Although other studies have sought to find a relationship between PELD and posttransplant outcome, 19,25 in this large cohort of patient, it is not surprising that the PELD score, which was developed only as a predictor or waiting list mortality, 26 would not be significant predictor of posttransplant outcome in an analysis that includes posttransplant events.…”
Section: Discussionmentioning
confidence: 91%
“…Although components of the MELD were thought to be a predictive factor in ALF (INR and bilirubin), the MELD score itself had poor specificity. 14 Rhee et al 15 eloquently showed that separate prioritizing systems for LT are needed in children with chronic liver disease and with PALF.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic categories for PALF based on previously defined criteria 1 included (1) acetaminophen associated ALF (2) autoimmune ALF (3) drug-induced ALF (4) ALF due to viral hepatitis (5) metabolic disease including Wilsons disease, mitochondrial disease, or disorders of fat metabolism diagnosis (6) other or (7) indeterminate ALF.…”
Section: Methodsmentioning
confidence: 99%